A systematic review of the prevalence of mental health symptoms and disorders in rugby players - Oftadeh-Moghadam, S.; Gorczynski, P. (Journal of Clinical Sport Psychology, 2024)
The aim of this systematic review was to investigate the prevalence of mental health symptoms and disorders in rugby players. Six electronic databases were searched in December 2020. Studies were included if they provided quantitative data on mental health symptoms and disorders and consisted of adult rugby players. Eight studies were included, covering symptoms of anxiety, depression, alcohol use/misuse, distress, sleeping/sleep disturbance, and eating disorders/adverse nutrition behaviors. Prevalence of mental health symptoms ranged from 6% (depression) to 68.8% (alcohol use/misuse). Most rates were similar to the general population, while symptoms of sleeping/sleep disturbance were lower, and symptoms of eating disorders/adverse nutrition behaviors and alcohol use/misuse were higher than the general population. One study included female rugby players. Epidemiological evidence comprising of rigorous diagnostic data and inclusive of gender, race, ethnicity, sexuality, and other protected characteristics is needed to inform future mental health support in this population.